Comparative Characteristics of Filtration Methods in the Processing of Medical Images - Orobinskyi, P.; Deineko, Z.; Lyashenko, V. (AJER, 2020)
Digital image analysis is one of the research tools in various fields. Such a tool plays a special role in the study of medical images. This is due to the specifics of the data that can be displayed on medical images. Examples of such images are digital images of E.coli. These images were obtained under a microscope. Processing of such images provides additional information. We consider the filtering procedure as a method of preliminary image processing. Among these filtration procedures, we examine classical filtration methods and filtration, which takes into account the geometric dimensions of E.coli. The article presents the results of experiments. A comparative description of various filtration procedures is given. This is based on various image comparison metrics. It is concluded that it is necessary to take into account the geometric dimensions of E.coli when using filtration procedures.
Keywords: digital image; filtering methods; E.coli; comparison metrics